Transforming Early Literacy: The Impact of Calistung Tutoring Programs on Student Comprehension in Trimulyo Village - Meisurie Meisurie; Aliffia Nurbaiti Janah; Al Laili Fatihatul Janah; Fini Septiani; Syara Della Sartika; Tri Suci Aini (Smart Society, 2023)
Education plays a crucial role in human resource development and serves as a foundation for national progress. However, the community in Trimulyo Village, South Lampung, still lacks awareness regarding the importance of education and the need for dedicated attention in children's learning. This program aims to enhance students' literacy and numeracy skills through a structured tutoring initiative. The study employs a community-based empowerment approach targeting five elementary school students aged 6-7 years in Trimulyo Village, Tanjung Bintang District. The program follows a three-stage method: Social Reflection, Observation, and Activity Implementation. The tutoring sessions were conducted three times a week. The primary objective was to provide additional learning support outside school hours, ensuring students become more familiar with the alphabet, numbers, and basic writing skills in a stress-free environment. The results indicate that students demonstrated significant improvements in reading comprehension, letter recognition, writing proficiency, vocabulary development, creativity enhancement through coloring activities, and overall focus during learning. Furthermore, this initiative contributed positively to the community by addressing educational challenges and supporting early childhood learning development in Trimulyo Village.